Drug utilization for common skin diseases: an outpatient based study - Mate, Vijay Haribhau; Gonarkar, Satish Balaji; Dhamani, Anjum Mehmood (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Drug utilization studies are useful for understanding the pattern of drug use in any particular healthcare set-up. This data gives an insight to improve the medical treatment at different layers in the health system. The oobjective of the present study was to assess drug utilization patterns by using core prescribing indicators of WHO and to assess most commonly observed skin disease in Dermatology out patients department (OPD) of tertiary care hospital. Methods: 246 prescriptions from Dermatology OPD were audited. Common skin diseases and the prescribing patterns were analysed from the prescriptions. Results: Average 2.4 drugs per prescription were seen in this study. 38.7% drugs were from National Essential Drug List of India. All the drugs were prescribed by brand names. The fixed dose combinations accounted for 20.6% drugs prescribed. Dosage, dose and duration of treatment were written for 100% of prescriptions. Around 44 different skin diseases were diagnosed amongst 246 patients predominantly cutaneous fungal infections, acne, dermatitis, eczema and psoriasis. About 591 different drugs were used mainly corticosteroids (21%), antibiotics (17%), anti-allergic (16%), antifungals (11%). Common skin conditions receiving corticosteroids were dermatitis (9.9%), eczema (9.1%). Antibiotics (17%), antifungals (11%) and antivirals (1%) were commonly used antimicrobial agents. 55.2% drugs were administered topically while 44.6% received orally. Conclusions: Prescriptions revealed a higher incidence of fungal and bacterial infections. All the medications were prescribed rationally. All prescriptions had proper dosage form, frequency of administration, duration of therapy and diagnosis. However, prescriber should be motivated for prescription of generic drugs and those from essential drug list.